Pengendalian Korosi Pipa perminyakan Dengan Menggunakan Inhibitor Korosi - Teuku Azhari Hassan; Komalasari Komalasari; Ida Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Addition of corrosion inhibitor volume into mixing produce oil and water is the methode to protect the inner pipe that can support reliability of the system. The used inhibitor is a kind of organic inhibitor which is generally contain of amin and used to resist corrosion rate for carbon steel which is a pipe material to distribute mixing produce oil and water. The relationship of fluide flow rate and addition of inhibitor volume is very important to understand. One of its parameter is corrosion rate measurement using corrosion coupon. The purpose of this study is to understand the effect of fluide flow rate and addition of inhibitor volume and to find the best condition of corrosion rate in the system. From the experimental results can be concluded that the highest fluide flow rate can increase the corrosion rate. The addition of corrosion inhibitor volume can resist the corrosion rate. The 2,5 gal/day inhibitor was the best inhibitor volume to resist the corrosion rate at variant fluide floe rate, which is 0,3 MPY for 40.000 bbl/day, 0,44 MPY for 60.000 bbl/day, 0,7 MPY for 80.000 bbl/day. Keyword: fluide flow rate, corrosion inhibitor, corrosion rate